Discursive navigation of employable identities in the narratives of former refugees - Greenbank, Emily (Studies in narrative ;, 2020)
"Incorporating both interview and workplace data, this book examines the discursive and social challenges that former refugees encounter as they navigate successes and failures in the New Zealand labour market. Over five chapters of microlevel discourse analysis - drawing on Bamberg & Georgakopoulou's (2008) positioning, and interactional sociolinguistic literature - themes emerge of narrative, social and cultural capital (Bourdieu, 1986), linguistic agency, and wider capital-D Discourses (Gee, 1990) surrounding refugeehood. Of particular interest in this study is the inclusion of a longitudinal study of former refugees' trajectories in the labour market, and the combination of both interview and authentic workplace interactional data, providing rich insight into the multiple and ongoing challenges new arrivals face in their negotiation of employability. This book will be of interest to those engaged in research around migration (particularly those focused on forced migration), employment, language and identity, and narrative identity"--